Tabus alimentares em pessoas com estomia no contexto amazônico - AMARAL, Máyra Patrícia do Carmo (2023)
Introduction: the increase in chronic diseases in recent years has rised the need for placement of ostomy. Changes occur in the lives of these individuals, and food suffers impact, through fasts or food taboo, people stop consuming certain foods, out of fear and as a atempt to prevent embarrassing situations. Objective: the present study sought the correlation of food taboo with nutritional status. Methodology: Individuals attended at the specialized reference unit in Belém, Pará, data collection occurred through the sociodemographic questionnaire, anthropometric evaluation, and the question if the person had a food taboo, if yes, were asked which. Results: 66% of the participants had food taboo, both men and women presented for shrimp and pork, but there was no significant correlation with nutritional status when evaluating Body Mass Index (p=0.13), adequacy of tritrital skinfold (p=0.26) and arm circunference (p=0,59) and Arm Muscle Circunference (p=0.74). Conclusion: Individuals with ostomy make exclusions in their diet, although no correlations with nutritional status have been found, this act can cause damage.